Composite fireproof door and manufacturing method
By using carbon fiber and carbon nanotube materials to make fire-proof boards in the fire-proof door, and filling them with porous modified molybdate nanomaterials, combined with the double-layer structure of perlite plates and glass magnesium plates, the existing fire-proof door core materials are easily deformed and collapsed under high temperature environments, and the efficient fire-proof insulation performance and smoking effect of the fire-proof door are achieved.
Patent Information
- Application Number
- CN202411939954.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing fireproof door core materials are prone to deform and collapse under high temperature environments, and have insufficient refractory and thermal insulation performance, making it difficult to meet the strict requirements of the market.
The fire-proof board is made of carbon fiber and carbon nanotube materials, and the inside is filled with porous modified molybdate nanomaterials. Combined with the double-layer structure of perlite plates and glass magnesium plates, it improves the high temperature resistance and smoking effect of the fire-proof door.
The overall quality of the fire door is light, good fire resistance, and has a strong smoking effect, while reducing the subsequent use cost.
Smart Images

Figure CN119686616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fireproof doors, in particular to a composite fireproof door and a manufacturing method thereof. Background Art
[0002] A fire door refers to a door that can meet the requirements of fire resistance stability, integrity and thermal insulation within a certain period of time. It is a fire-resistant partition with a certain fire resistance installed in fire compartments, evacuation stairwells, vertical shafts, etc. It is specifically used to isolate fire sources in residential buildings and plays a huge role in fire fighting. Once a fire occurs, people can get a chance to escape through the fire door.
[0003] At present, the commonly used fire doors are mostly steel fire doors, steel-wood fire doors or fire doors made of metal and inorganic materials. Their materials are all non-combustible substances and have high resistance to high temperature deformation. However, steel fire doors are very thick and heavy, and it is very inconvenient to open and close. In addition, due to the good thermal conductivity of metal, the temperature of the back-fire surface of the metal fire door will rise rapidly in the event of a fire, which will cause great obstacles to personnel evacuation and fire rescue. Fire doors are mainly composed of door frames, door cores, artificial boards and hardware. From the perspective of fire prevention and heat insulation, the fire door core plays the most important and critical role.
[0004] From the requirements of the new fire door standard GB12955-2008 for the core material of fire doors, it can be seen that the core material of fire doors needs to have the following properties: (1) During the burning process of a large fire, the core material of the fire door needs to maintain thermal insulation and integrity, and the back-fire surface of the fire door core is basically not deformed. This is the most important property that the core material must have. (2) The core material must be light, otherwise the fire door will be too heavy, which will affect production, transportation, installation and use. The most suitable density of the core material is within 0.4g / cm3. Therefore, the core of the fire door must have a porous structure. (3) The core material must have the necessary strength and toughness. However, it is well known that the strength and toughness of porous materials decrease very quickly with the decrease in density. (4) The core material must be non-toxic and harmless. During the fire-retardant process, the smoke toxicity meets the ZA2 level requirements. In addition, in order to meet market requirements, it is also necessary to have high productivity and low cost.
[0005] At present, the main fire door core materials on the market are porous air-entraining magnesium oxide / magnesium chloride board (abbreviated as porous air-entraining magnesium oxychloride board) and perlite board, but they have defects such as disintegration during burning and corrosiveness of brine. Perlite board has the problem of very serious shrinkage and deformation during burning and poor fireproof and heat insulation. Prior art CN101555121A discloses a new composite perlite board for fireproof and heat insulation and its production method, which has excellent mechanical strength and good thermal insulation and sound insulation capabilities, but its heat insulation and fireproof performance is difficult to meet the increasingly stringent requirements of the market. At present, the fire resistance and heat insulation limit of the fireproof roller shutter prepared by the common fire door core materials on the market is tested according to the provisions of GB / T 7633 in the national standard GB14102-2005, and is calculated by the method of judging the loss of fire resistance and heat insulation by the average temperature rise. Generally, the fire resistance limit does not exceed 2 hours.
[0006] At the same time, in order to further improve the fireproof and heat-insulating performance of the fireproof door core, a large number of companies in the industry have conducted many beneficial explorations. For example, CN115304344A discloses a fireproof and heat-insulating filler for steel fireproof doors. This patent adds a water-retaining agent to the common heat-insulating and fireproof core material. Water molecules are retained in the filler by the polymer water-retaining agent. When one side of the door panel is exposed to fire, the hardened filler absorbs heat and releases water molecules at the same time. The water molecules evaporate and take away a large amount of heat, thereby effectively delaying the heating rate of the entire door panel and effectively improving the fireproof and heat-insulating performance. However, since the water-retaining agent contains a large amount of water, if the amount is too much, it will first lead to too low strength of the core molding material. In addition, when exposed to fire, while a large amount of water evaporates, the water-retaining agent shrinks to form a large number of voids, resulting in a sharp drop in the strength of the fireproof core material, which is prone to collapse due to burning shrinkage and deformation.
[0007] During the research process, the inventors found that molybdenum and its inorganic compounds such as nickel molybdate have very high melting points and high temperature resistance. In the air, molybdenum can withstand high temperatures above 600°C, and under inert gas, the high temperature resistance of molybdenum and its inorganic compounds can reach above 2000°C. At the same time, the melting point of materials such as carbon fiber or carbon nanotubes is as high as 3000°C, and they are light in weight and high in strength, which can improve the above-mentioned shortcomings of easy deformation or heavy weight of calcium carbonate and carbon fiber composite doors in the prior art. Therefore, the inventors combined the basic process and principle of composite materials, applied the above materials to fire doors, and made a composite fire door. Summary of the invention
[0008] The purpose of the present invention is to provide a composite fire door, which has a light overall weight, good fireproof performance, and a strong smoking effect. At the same time, the manufacturing process provided by the present invention is simple to operate and convenient and easy to operate.
[0009] To achieve the above object, the present invention provides the following technical solutions: A composite fire door, comprising a door skeleton, a wooden board and a filled fireproof core material. The door skeleton is a U-shaped composite structure of calcium carbonate and carbon fiber. A plurality of connecting plates are integrally arranged on the inner side of the door skeleton. The connecting plates are arranged in a plurality along the width direction of the door skeleton. A fireproof board is further installed between the door skeleton and the wooden board. The fireproof board is arranged in layers and includes carbon fiber boards on both sides, a fireproof skeleton inside and a fireproof filler coated inside the carbon fiber boards. The fireproof filler is a porous modified molybdate nanomaterial. The fireproof core material is a double-layer structure, including a magnesium oxychloride board and a perlite board bonded to one side of the magnesium oxychloride board. The perlite board is arranged facing the carbon fiber layer side. There are two wooden boards, and the two wooden boards cover both sides of the door skeleton. One wooden board is bonded to one side of the door skeleton, and the other wooden board is adhesively fixed to the carbon fiber board on the other side.
[0010] In the present invention, fireproof solid wood is used as the panel to improve its aesthetics. At the same time, a calcium carbonate and carbon fiber composite door skeleton is used inside in combination with a fireproof board for fire prevention and smoke absorption. Specifically, the melting point temperatures of the carbon fiber boards and carbon fiber tubes are both above 3000 °C, and the melting point temperatures of the arranged perlite board and magnesium oxychloride board are both above 2000 °C. Therefore, the fireproof effect is good, and the large number of pores inside combined with carbon nanotubes and porous modified molybdate nanomaterials can have a good smoke absorption effect.
[0011] At the same time, the door skeleton is made of a composite of calcium carbonate material and carbon fiber. The calcium carbonate uses high-density calcium carbonate with a bulk density of 0.6 g / ml and a melting point of about 1300 °C. At the same time, combined with the reinforcement of carbon fiber, the overall structural strength is high, and the quality is lower than that of the existing steel door skeleton.
[0012] As a preferred embodiment of the present invention, the material of the fireproof skeleton is carbon nanotubes after bonding. The fireproof skeleton includes a plurality of carbon nanotube group rods. Correspondingly, the carbon nanotube group rods are in an "L" shape or a "U" shape, and screw mounting holes are provided on the side of the carbon nanotube group rods.
[0013] As a preferred embodiment of the present invention, the side of the connecting plate is provided with the same screw mounting holes. There is a gap after the connecting plate is installed with the steel rods on both sides. The connecting plate and the carbon nanotube group rods are connected by using a double-headed threaded rod. The double-headed threaded rod passes through the screw mounting holes on one side of the carbon nanotube group rod of the connecting plate, the screw mounting holes on the connecting plate, and the screw mounting holes on the carbon nanotube group rod on the other side in sequence and is locked by a nut.
[0014] As a preferred embodiment of the present invention, a plurality of grooves are provided on the side of the wooden board bonded to the door skeleton. At the positions corresponding to the grooves, a plurality of convex ribs are welded on the side of the door skeleton. A clamping plate is inserted into the inner side of the wooden board bonded to the carbon fiber board. The clamping plate corresponds to the gap after the connecting plate is installed with the steel rods on both sides. A slot is provided on the clamping plate, and a TPU elastic ring is embedded at the bottom of the slot.
[0015] As a preferred embodiment of the present invention, a mounting plate is welded between the inner walls of the door frame. A concealed door closer is installed on the mounting plate. A wooden strip is wrapped on the side of the concealed door closer. The upper surface of the wooden strip is flush with the upper surface of the door frame. The wooden strip is bonded to the mounting plate. A lock hole for installing a door lock is provided on the wooden board close to the carbon fiber board side.
[0016] As a preferred embodiment of the present invention, nitrogen is filled inside the porous modified molybdate nanomaterial. Nitrogen fills the pores inside the porous modified molybdate nanomaterial. The outside of the porous modified molybdate nanomaterial is sealed with an epoxy resin having a high molecular weight.
[0017] As a preferred embodiment of the present invention, the perlite board is bonded to the magnesium oxychloride board. A number of concave holes are provided inside the perlite board. A magnesium oxychloride tube is connected between two adjacent concave holes. A number of through holes are provided on the side of the magnesium oxychloride tube.
[0018] The present invention also provides a manufacturing method of a composite fire door. Based on the foregoing composite fire door, the following manufacturing steps are specifically included: (1). Manufacture the door frame. According to the required door length and width dimensions, manufacture a mold. Lay multiple layers of carbon fiber mesh boards in the mold in the height direction. Pour molten calcium carbonate inside and take it out after cooling. At the same time, integrally form a connecting plate, a mounting plate and a convex rib to form a U-shaped door frame; (2). Perforate the connecting plate for screw installation. One end of the connecting plate abuts against the end of the door frame, and the other end reserves a mounting plate position with the end of the door frame; (3). Manufacture the carbon nanotube group rod and perforate the side of the carbon nanotube group rod. The carbon nanotube group rod is made into an "L" shape or a "U" shape; (4). Prepare the porous modified molybdate nanomaterial; (5). Adhere the woven carbon fiber board to one side of the carbon nanotube group rod obtained in step (3) with an inorganic silica adhesive. After adhering one side, fill the inside with the porous modified molybdate nanomaterial prepared in step (4). After filling and keeping it full, then adhere the carbon fiber board on the other side to complete the production of the fireproof board; (6). Install the manufactured fireproof boards one by one inside the door frame and lock them with double-headed threaded rods and nuts; (7). Weld the mounting plate and weld the mounting plate on the top of all the connecting plates for installing a concealed door closer; (8). Manufacture the fireproof core material and fill it in the position between the fireproof board and the door frame; (9). Bond the wooden board and bond the wooden board on the convex rib side of the corresponding door frame with an inorganic silica adhesive; (10) Install the door locks and the conventional equipment necessary for fire doors, and then bond the wooden board to the fire board using an inorganic silicone compound to complete the fire door production.
[0019] As a preferred embodiment of the present invention, the specific steps of step ③ include: ①. Use PET resin to make tubular mold; ②. Coat all surfaces of the mold with inorganic silicone compound; ③. After spreading evenly, put it into the single-walled nanotube powder pile, stir the powder pile, and take it out after stirring to obtain the carbon nanotube rod containing PET resin; ④, calcining the carbon nanotube rods in step ③, maintaining the temperature at 220°C to 260°C, calcining time 1h to 3h, and collecting the carbon nanotube rods; ⑤. Soak in ethylene glycol for 1h to 3h, rinse repeatedly with deionized water 5 times, dry at 50℃ for 1h to 3h, and collect; ⑥. Grind the collected carbon nanotube rods and roughen the surface to obtain the desired carbon nanotube rods.
[0020] As a preferred solution of the present invention, the specific steps of step ④ include: ①. Using raw materials of molybdenum disulfide and manganese acetate, measure 40 ml of ethylene glycol solution and place it in a beaker, then weigh 0.92 g of molybdenum disulfide and 0.49 g of manganese acetate and add them to the beaker containing the aforementioned ethylene glycol solution, stir the solution under vigorous magnetic stirring for 30 minutes to form a uniform mixture, then add 6.0 g of polyvinyl pyrrolidone to the mixed solution, heat it to 60°C, and continue stirring for 60 minutes. After the polyvinyl pyrrolidone is completely dissolved, add 9.6 g of urea and continue stirring for 60 minutes. Subsequently, transfer the resulting solution to a reactor and keep it in an electrically heated blast drying oven at 220°C for 48 hours; use a permanent magnet to collect the wet precipitate, and then rinse it three times with deionized water to remove impurities. Finally, dry the sample in a vacuum oven at 60°C for 24 hours to obtain porous molybdate nanospheres; ②, scale up according to step ① to prepare a large number of porous molybdate nanospheres; ③, introducing nitrogen into the porous molybdate nanospheres; ④, during the nitrogen introduction process, add epoxy resin with a mass ratio of 0.75 to the porous molybdate nanospheres, stir evenly, and obtain porous modified molybdate nanospheres; ⑤. Dry the porous modified molybdate nanospheres obtained in step ④ in a drying tower for 48 hours, maintaining the temperature at 50° C., and collect for later use.
[0021] As a preferred solution of the present invention, the side of the acid electrolyte mixing box is rotatably connected to a rotating shaft, the rotating shaft extends into the interior of the acid electrolyte mixing box, the rotating shaft is located inside the acid electrolyte mixing box and a fixed plate is fixed to the end thereof, a plurality of fixed plates are provided along the circumferential direction of the rotating shaft, the fixed plate is rotatably connected to an agitating blade away from the end of the rotating shaft, a plurality of agitating blades are provided, and the end of the rotating shaft extending out of the acid electrolyte mixing box is connected to a motor.
[0022] In summary, the beneficial technical effects of the present invention are: 1. Improve the overall structure of the fire door, and use steel plates, wood boards and fireproof boards to make them. The fireproof boards are made of carbon fiber and carbon nanotube materials, which have strong support performance and are not easy to deform. They also have built-in fireproof fillers, which increase the fireproof performance while improving the strength and reducing the overall quality; 2. The fireproof filler is made of nickel molybdate nanomaterials with high heat resistance. After modification, it has a porous structure. Inert gases such as nitrogen are sealed inside. The sealed epoxy resin is fusible. In case of fire, nitrogen is easily released, which further improves the heat resistance of nickel molybdate nanomaterials. At the same time, the porous properties can effectively increase the amount of smoke. 3. Improve the fireproof core material. On the basis of the existing materials, expand the holes inside the perlite board to further increase the smoking capacity; 4. The porous modified nickel molybdate nanomaterial can be recycled and reused multiple times, and the wooden board and fireproof board structure can be disassembled and reassembled, reducing the subsequent use cost; 5. Use high-density calcium carbonate and carbon fiber composite materials to replace the existing steel door frame, which has excellent fire resistance, improved overall strength, and further reduced quality; 6. The manufacturing process includes the synthesis of porous modified nickel molybdate nanomaterials and the production of carbon nanotube rods. The overall processing technology is simple and convenient to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification, but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 This is a structural schematic diagram of a composite fire door and a manufacturing method of this embodiment; Figure 2 This is a composite fire door and a manufacturing method of the present embodiment. Figure 1 Schematic diagram of the explosion structure; Figure 3 This is a schematic diagram of the connection between a door frame and a fireproof board of a composite fireproof door and a manufacturing method of the present embodiment; Figure 4 It is a schematic diagram of the interior of a fireproof board of a composite fireproof door and a manufacturing method of the present embodiment; Figure 5It is an internal schematic diagram of the fireproof core material of a composite fireproof door and its manufacturing method in this embodiment; Figure 6 It is a scanning electron microscope schematic diagram of the porous modified nickel molybdate nanomaterial in the protective filler of a composite fireproof door and its manufacturing method in this embodiment.
[0024] In the figure, 1 is the door skeleton; 2 is the wooden board; 3 is the connecting plate; 4 is the fireproof board; 5 is the carbon fiber board; 6 is the fireproof skeleton; 7 is the fireproof filler; 8 is the magnesium oxychloride board; 9 is the perlite board; 10 is the screw installation hole; 11 is the double-headed threaded rod; 12 is the nut; 13 is the groove; 14 is the convex rib; 15 is the clamping plate; 16 is the slot; 17 is the TPU elastic ring; 18 is the mounting plate; 19 is the concealed door closer; 20 is the wooden strip; 21 is the concave hole; 22 is the magnesium oxychloride tube; 23 is the through hole. Detailed implementation manners
[0025] The present invention will be further described in detail below with reference to the accompanying drawings.
[0026] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0027] Please refer to Figure 1-6 , the present invention provides a technical solution: a composite fireproof door and its manufacturing method, including a door skeleton 1, a wooden board 2 and a filled fireproof core material. The door skeleton 1 is a composite structure of U-shaped calcium carbonate and carbon fiber. A number of connecting plates 3 are integrally arranged inside the door skeleton 1. A number of connecting plates 3 are arranged along the width direction of the door skeleton 1. A fireproof board 4 is also installed between the door skeleton 1 and the wooden board 2. The fireproof board 4 is arranged in layers. The fireproof board 4 includes carbon fiber boards 5 on both sides, a fireproof skeleton 6 inside, and a fireproof filler 7 coated inside the carbon fiber boards 5. The fireproof filler 7 is a porous modified molybdate nanomaterial. The fireproof core material is a double-layer structure, including a magnesium oxychloride board 8 and a perlite board 9 bonded to one side of the magnesium oxychloride board 8. The perlite board 9 is arranged towards the carbon fiber layer side. There are two wooden boards 2. The two wooden boards 2 cover both sides of the door skeleton 1. One of the wooden boards 2 is bonded to one side of the door skeleton 1, and the other wooden board 2 is adhesively fixed to the carbon fiber board 5 on the other side.
[0028] The material of the fireproof skeleton 6 is carbon nanotubes after bonding. The fireproof skeleton 6 includes a number of carbon nanotube group rods. Correspondingly, the carbon nanotube group rods are in an "L" shape or a "U" shape. Screw installation holes 10 are provided on the side of the carbon nanotube group rods.
[0029] The side of the connecting plate 3 is provided with the same screw mounting holes 10. There is a gap after the connecting plate 3 is installed with the steel rods on both sides. The connecting plate 3 and the carbon nanotube group rod are connected by using a double-headed threaded rod 11. The double-headed threaded rod 11 sequentially passes through the screw mounting holes 10 on one side of the carbon nanotube group rod of the connecting plate 3, the screw mounting holes 10 on the connecting plate 3, and the screw mounting holes 10 on the carbon nanotube group rod on the other side and is locked by nuts 12.
[0030] In this embodiment, four groups of screw mounting holes 10 are provided on the side of the connecting plate 3 along the length direction of the connecting plate 3. Each group has two screw mounting holes 10. Along the width direction of the connecting plate 3, the door frame 1 is of a U-shaped structure. Grooves for installing concealed hinges are cut out on both sides of it, and at the same time, both sides are not covered by the wooden board 2. The wooden board 2 covers both sides of its upper and lower surfaces. Specifically, the wooden board 2 used is fireproof solid wood.
[0031] Inside the door frame 1, a mounting plate 18 for installing a concealed door closer 19 is welded. Except for the area of the concealed door closer 19 at the top, the rest is covered by the wooden board 2. Specifically, mounting plates 18 are welded between the inner walls of the door frame 1. A concealed door closer 19 is installed on the mounting plate 18. A wooden strip 20 is provided on the side of the concealed door closer 19. The upper surface of the wooden strip 20 is flush with the upper surface of the door frame 1. The wooden strip 20 is bonded to the mounting plate 18. A lock hole for installing a door lock is provided on the wooden board 2 near the carbon fiber board 5 side.
[0032] In the installation of the door frame 1 and the template, several grooves 13 are provided on the side of the wooden board 2 bonded to the door frame 1. At the positions corresponding to the grooves 13, several convex ribs 14 are welded on the side of the door frame 1. Correspondingly, when installing the wooden board 2, a slot is made along the vertical direction of the wooden board 2, and the position of the slot coincides with the position of the convex rib 14. Thus, when using an inorganic silicone adhesive for bonding, the bonding area is increased, effectively improving the installation stability of the wooden board 2; on the other side, a clamping plate 15 is inserted into the inner side of the wooden board 2 bonded to the carbon fiber board 5. The clamping plate 15 corresponds to the gap after the connecting plate 3 is installed with the steel rods on both sides. A slot 16 is provided on the clamping plate 15, and a TPU elastic ring 17 is embedded at the bottom of the slot 16. Since the connecting plate 3 is fixed inside the door frame 1 by welding, the position of the connecting plate 3 is fixed. When installing the fireproof board 4, the width of each fireproof board 4 is fixed, and thus the width of the above-mentioned gap is determined. When processing this side of the wooden board 2, the clamping plate 15 is inserted and installed on the wooden board 2. Two clamping plates 15 are in a group. Each clamping plate 15 is clamped on both sides of the connecting plate 3. When it comes into contact with the double-headed threaded rod 11 among them, the double-headed threaded rod 11 enters along the slot 16 of the clamping plate 15. At the same time, the bottom uses the TPU elastic ring 17 to resist the double-headed threaded rod 11, increasing the friction between the slot 16 and the double-headed threaded rod 11 and avoiding the double-headed threaded rod 11 from wearing the wooden board 2.
[0033] The porous modified molybdate nanomaterial is filled with nitrogen gas, which fills the pores inside the porous modified molybdate nanomaterial. The outside of the porous modified molybdate nanomaterial is sealed with an epoxy resin having a high molecular weight.
[0034] On the basis of the fire prevention of the carbon fiber board 5, carbon fiber tube, perlite board 9 and magnesium oxychloride board 8, the inside of the fireproof board 4 is further filled with a porous modified molybdate nanomaterial, and then the outside of the porous modified molybdate nanomaterial is sealed with an epoxy resin at the same time. When the temperature rises upon encountering fire, due to the low melting point of the epoxy resin with a high molecular weight, around 75 °C, when the temperature increases, after it melts, it can release the nitrogen gas inside the porous modified molybdate nanomaterial, reduce the oxygen content in the surrounding air, contain the fire, and improve the fireproof performance of this fireproof door at the same time. At the same time, after the porous modified molybdate nanomaterial releases nitrogen gas, it has many internal pore spaces and can absorb smoke, thereby reducing the smoke discharge amount. At the same time, combined with the physical and chemical properties of molybdate, under inert gas, the high temperature resistance temperature further increases. Therefore, nitrogen gas can also place the porous modified molybdate nanomaterial within the range of inert gas, further improving the fireproof performance.
[0035] At the same time, the fireproof core material is a combination of a magnesium oxychloride board 8 and a perlite board 9. The perlite board 9 is bonded to the magnesium oxychloride board 8. A number of concave holes 21 are provided inside the perlite board 9. A magnesium oxychloride tube 22 is connected between two adjacent concave holes 21. A number of through holes 23 are provided on the side of the magnesium oxychloride tube 22. Therefore, the holes on the perlite board 9 increase, and at the same time, a magnesium oxychloride tube 22 with multiple through holes 23 is also provided between the concave holes 21. Further combined with the above-mentioned porous modified molybdate nanomaterial, the smoke absorption amount can be further improved.
[0036] Based on the fireproof door structure provided in this embodiment, in this embodiment, the following manufacturing steps are specifically adopted to manufacture the composite fireproof door, and its process includes: (1). Manufacture the door frame 1. According to the required door length and width dimensions, manufacture a mold, lay multiple layers of carbon fiber mesh boards in the mold along the height direction, pour molten calcium carbonate inside, take it out after cooling, and integrally form the connecting plate 3 and the convex rib 14 at the same time to form a U-shaped door frame 1; (2). Perforate the connecting plate 3 for screw installation. One end of the connecting plate 3 abuts against the end of the door frame 1, and the other end reserves the position of the mounting plate 18 with the end of the door frame 1; (3). Manufacture the carbon nanotube group rod and perforate the side of the carbon nanotube group rod, and the carbon nanotube group rod is manufactured in an "L" shape or a "U" shape; (4). Prepare the porous modified molybdate nanomaterial; (5) One side of the carbon nanotube rod obtained in step ③ is bonded with the woven carbon fiber plate 5 using an inorganic silica gel mixture. After bonding one side, the porous modified molybdate nanomaterial prepared in step ④ is filled inside. After the filling is maintained in a full state, the other side of the carbon fiber plate 5 is bonded to complete the production of the fireproof board 4; (6) Install the manufactured fireproof panels 4 one by one inside the door frame 1 and lock them with the double-headed threaded rod 11 and the nut 12; (7) Weld the mounting plate 18 to the top of all the connecting plates 3 to prepare for the installation of the hidden door closer 19; (8) Prepare fireproof core material and fill it between the fireproof board 4 and the door frame 1; (9) Bonding the wooden board 2: Bonding the wooden board 2 on the side of the convex edge 14 of the door frame 1 using an inorganic silica gel mixture; (10) Install the conventional equipment necessary for door locks and fireproof doors, and then bond the wooden board 2 to the fireproof board 4 through an inorganic silica gel compound to complete the production of the fireproof door.
[0037] The specific steps of step ③ include: ①. Use PET resin to make tubular mold; ②. Coat all surfaces of the mold with inorganic silicone compound; ③. After spreading evenly, put it into the single-walled nanotube powder pile, stir the powder pile, and take it out after stirring to obtain the carbon nanotube rod containing PET resin; ④, calcining the carbon nanotube rods in step ③, maintaining the temperature at 220°C, calcining time for 3 hours, and collecting the carbon nanotube rods; ⑤. Soak in ethylene glycol for 3 hours, rinse with deionized water for 5 times, dry at 50℃ for 3 hours, and collect; ⑥. Grind the collected carbon nanotube rods until the inner wall thickness of the carbon nanotube rods is 2 mm, and perform surface roughening to obtain the desired carbon nanotube rods.
[0038] Among them, the specific steps of step ④ include: ①. Using raw materials of molybdenum disulfide and manganese acetate, measure 40 ml of ethylene glycol solution and place it in a beaker, then weigh 0.92 g of molybdenum disulfide and 0.49 g of manganese acetate and add them to the beaker containing the aforementioned ethylene glycol solution, stir the solution under vigorous magnetic stirring for 30 minutes to form a uniform mixture, then add 6.0 g of polyvinyl pyrrolidone to the mixed solution, heat it to 60°C, and continue stirring for 60 minutes. After the polyvinyl pyrrolidone is completely dissolved, add 9.6 g of urea and continue stirring for 60 minutes. Subsequently, transfer the resulting solution to a reactor and keep it in an electrically heated blast drying oven at 220°C for 48 hours; use a permanent magnet to collect the wet precipitate, and then rinse it three times with deionized water to remove impurities. Finally, dry the sample in a vacuum oven at 60°C for 24 hours to obtain porous nickel molybdate nanospheres; ②, scale up according to step ① to prepare a large number of porous nickel molybdate nanospheres; ③, introducing nitrogen into the porous nickel molybdate nanospheres; ④. During the nitrogen introduction process, epoxy resin was added in a mass ratio of 0.75 to the porous nickel molybdate nanospheres, and the mixture was stirred evenly to obtain porous modified nickel molybdate nanospheres; ⑤. Dry the porous modified molybdate nanospheres obtained in step ④ in a drying tower for 48 hours, maintaining the temperature at 50° C., and collect for later use.
[0039] The porous molybdate nanospheres prepared by the above preparation method were photographed by scanning electron microscope, and the following Figure 5 From the scanning electron microscope image shown, it can be observed that it is a secondary structure formed by multiple clusters of particles with uniform particle size distribution. Due to the clustering of multiple particles, a large number of gap holes are formed inside each secondary sphere, so it can be used as a storage carrier for nitrogen. At the same time, the melting point of nickel molybdate itself is about 1000°C.
[0040] In actual testing, the steel plate in this application was limited to a thickness of 2 mm, a width of 1270 mm, and a length of 3072 mm. The above-mentioned process was used for processing and manufacturing, and the resulting composite fire door was subjected to the American standard UL10C test and successfully passed the test. The smoke emission was also less visible than that of existing fire doors.
[0041] In this embodiment, the fireproof wooden board 2 bonded and fixed to the fireproof board 4 is installed facing the interior. If the wooden board 2 is damaged, it can be replaced. At the same time, after the internal fireproof board 4 is damaged, the carbon fiber board 5 can be opened and refilled with nitrogen-sealed porous modified nickel molybdate nanospheres for use. Therefore, the composite fireproof door provided in this embodiment can be conveniently used multiple times.
[0042] In particular, the internal door frame 1 of the composite fireproof door is a composite of calcium carbonate and carbon fiber, which can be applied to various types of machining, and then various existing conventional hidden hardware such as hidden fireproof hinges can be installed, which can further improve the sound insulation performance.
[0043] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0044] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite fireproof door, comprising a door frame (1), a wood board (2) and a filled fireproof core material, characterized in that: The door frame (1) is a calcium carbonate and carbon fiber composite structure in a U-shaped shape. A number of connecting plates (3) are integrally provided inside the door frame (1). A number of connecting plates (3) are provided along the width direction of the door frame (1). A fireproof board (4) is also installed between the door frame (1) and the wooden board (2). The fireproof board (4) is arranged in layers. The fireproof board (4) includes carbon fiber boards (5) on both sides, a fireproof skeleton (6) inside, and a fireproof filler (7) coated inside the carbon fiber boards (5). The fireproof filler (7) is a porous modified molybdate nanomaterial. The fireproof core material is a double-layer structure, including a magnesium oxychloride board (8) and a perlite board (9) bonded to one side of the magnesium oxychloride board (8). The perlite board (9) is arranged towards the carbon fiber layer side. Two wooden boards (2) are provided. The two wooden boards (2) cover both sides of the door frame (1). One of the wooden boards (2) is bonded to one side of the door frame (1), and the other wooden board (2) is adhesively fixed to the carbon fiber board (5) on the other side.
2. A composite fire door according to claim 1, characterized in that: The fireproof board (4) is in an "L" shape or a "U" shape. The material of the fireproof skeleton (6) is carbon nanotubes after bonding. The fireproof skeleton (6) includes a number of carbon nanotube group rods. Correspondingly, the carbon nanotube group rods are in an "L" shape or a "U" shape. Screw mounting holes (10) are provided on the side of the carbon nanotube group rods.
3. A composite fire door according to claim 2, characterized in that: The side of the connecting plate (3) is provided with the same screw mounting holes (10). There is a gap after the connecting plate (3) is installed with the steel rods on both sides. The connecting plate (3) and the carbon nanotube group rods are connected by using a double-headed threaded rod (11). The double-headed threaded rod (11) sequentially passes through the screw mounting holes (10) on the carbon nanotube group rod on one side of the connecting plate (3), the screw mounting holes (10) on the connecting plate (3), and the screw mounting holes (10) on the carbon nanotube group rod on the other side and is locked by a nut (12).
4. A composite fire door according to claim 1, characterized in that: A number of grooves (13) are provided on the side of the wooden board (2) bonded to the door frame (1). At the positions corresponding to the grooves (13), a number of convex ribs (14) are welded on the side of the door frame (1). A clamping plate (15) is inserted inside the wooden board (2) bonded to the carbon fiber board (5). The clamping plate (15) corresponds to the gap after the connecting plate (3) is installed with the steel rods on both sides. A slot (16) is provided on the clamping plate (15). A TPU elastic ring (17) is embedded at the bottom of the slot (16).
5. A composite fire door according to claim 1, characterized in that: A mounting plate (18) is welded between the inner walls of the door frame (1). A concealed door closer (19) is installed on the mounting plate (18). A wooden strip (20) is coated on the side of the concealed door closer (19). The upper surface of the wooden strip (20) is flush with the upper surface of the door frame (1). The wooden strip (20) is bonded to the mounting plate (18). A lock hole for installing a door lock is provided on the wooden board (2) close to the carbon fiber board (5) side.
6. A composite fire door according to claim 1, characterized in that: The porous modified molybdate nanomaterial is filled with nitrogen inside. The nitrogen fills the holes inside the porous modified molybdate nanomaterial. The outside of the porous modified molybdate nanomaterial is sealed with an epoxy resin with a high molecular weight.
7. A composite fire door according to claim 1, characterized in that: The perlite board (9) is bonded to the magnesite board (8). A number of concave holes (21) are provided inside the perlite board (9). A magnesite tube (22) is connected between two adjacent concave holes (21). A number of through holes (23) are provided on the side of the magnesite tube (22).
8. A method for manufacturing a composite fire door, based on the structure of claims 1-7, characterized in that: Specifically, it includes the following manufacturing steps: (1) Manufacture the door frame. According to the required door length and width dimensions, manufacture a mold. Lay multiple layers of carbon fiber mesh boards inside the mold in the height direction. Pour molten calcium carbonate inside and take it out after cooling. At the same time, integrally form a connecting plate, a mounting plate and a convex rib to form a U-shaped door frame; (2) Punch holes in the connecting plate for screw installation. One end of the connecting plate abuts against the end of the door frame, and the other end reserves the position of the mounting plate at the end of the door frame; (3) Manufacture the carbon nanotube group rod and punch holes on the side of the carbon nanotube group rod. The carbon nanotube group rod is manufactured in an "L" shape or a "U" shape; (4) Prepare the porous modified molybdate nanomaterial; (5) On one side of the carbon nanotube group rod obtained in step (3), adhesively bond the woven carbon fiber board with inorganic silicone adhesive. After one side is adhesively bonded, fill the inside with the porous modified molybdate nanomaterial prepared in step (4). After filling and keeping it full, adhesively bond the carbon fiber board on the other side to complete the production of the fireproof board; (6) Install the manufactured fireproof boards one by one inside the door frame and lock them with double-headed threaded rods and nuts; (7) Weld the mounting plate and weld the mounting plate on the top of all the connecting plates to prepare for installing the concealed door closer; (8) Manufacture the fireproof core material and fill it in the position between the fireproof board and the door frame; (9) Bond the wood board. Bond the wood board on the convex rib side of the corresponding door frame and use inorganic silicone adhesive for bonding; (10) Install the door lock and the conventional equipment necessary for the fireproof door, and then bond the wood board to the fireproof board with inorganic silicone adhesive to complete the production of the fireproof door.
9. The method for manufacturing a composite fire door according to claim 8, characterized in that: The specific steps of step (3) include: ①. Use PET resin to manufacture a tubular mold; ②. Coat all surfaces of the mold with inorganic silicone adhesive; ③. After applying evenly, put it into the single-walled carbon nanotube powder pile and stir the powder pile. After stirring, take it out to obtain a carbon nanotube group rod containing PET resin; ④. Calcine the carbon nanotube group rod in step (3), keep the temperature at 220°C to 260°C, and the calcination time is 1h to 3h. Collect the carbon nanotube group rod; ⑤. Soak it with ethylene glycol for 1h to 3h. After soaking, repeatedly rinse it 5 times with deionized water and dry it at 50°C for 1h to 3h. Collect it; ⑥. Grind the collected carbon nanotube group rod and roughen the surface to obtain the required carbon nanotube group rod.
10. The method for manufacturing a composite fire door according to claim 8, characterized in that: The specific steps of step (4) include: ①. Using raw materials of molybdenum disulfide and nickel acetate, measure 40 ml of ethylene glycol solution and place it in a beaker, then weigh 0.92 g of molybdenum disulfide and 0.51 g of nickel acetate and add them to the beaker containing the aforementioned ethylene glycol solution, stir the solution under vigorous magnetic stirring for 30 minutes to form a uniform mixture, then add 6.0 g of polyvinyl pyrrolidone to the mixed solution, heat it to 60 ° C, and continue stirring for 60 min. After the polyvinyl pyrrolidone is completely dissolved, add 9.6 g of urea and continue stirring for 60 min. Subsequently, transfer the resulting solution to a reactor and keep it in an electrically heated blast drying oven at 220 ° C for 48 h; use a permanent magnet to collect the wet precipitate, and then rinse it three times with deionized water to remove impurities. Finally, dry the sample in a vacuum oven at 60 ° C for 24 hours to obtain porous nickel molybdate nanospheres; ②, scale up according to step ① to prepare a large number of porous nickel molybdate nanospheres; ③, introducing nitrogen into the porous nickel molybdate nanospheres; ④. During the nitrogen introduction process, epoxy resin was added in a mass ratio of 0.75 to the porous nickel molybdate nanospheres, and the mixture was stirred evenly to obtain porous modified nickel molybdate nanospheres; ⑤. Dry the porous modified nickel molybdate nanospheres obtained in step ④ in a drying tower for 48 hours, maintaining the temperature at 50° C., and collect for later use.
Citation Information
Patent Citations
Novel composite perlite board for fire prevention and heat insulation and manufacturing method thereof
CN101555121A
Fireproof heat-insulation filler for steel fireproof door and application method of fireproof heat-insulation filler
CN115304344A
Fireproof door for concert hall
CN105257183A
Fireproof door plate structure with C-shaped framework
CN217176392U
Steel fireproof door with high fire resistance and heat insulation property
CN217632138U